High associative neuron numbers could drive cognitive performance in corvid species. Issue 10 (25th January 2022) - Ströckens, Felix; Neves, Kleber; Kirchem, Sina; Schwab, Christine; Herculano‐Houzel, Suzana; Güntürkün, Onur
Abstract: Corvids possess cognitive skills, matching those of nonhuman primates. However, how these species with their small brains achieve such feats remains elusive. Recent studies suggest that cognitive capabilities could be based on the total numbers of telencephalic neurons. Here we extend this hypothesis further and posit that especially high neuron counts in associative pallial areas drive flexible, complex cognition. If true, avian species like corvids should specifically accumulate neurons in the avian associative areas meso‐ and nidopallium. To test the hypothesis, we analyzed the neuronal composition of telencephalic areas in corvids and noncorvids (chicken, pigeons, and ostriches—the species with the largest bird brain). The overall number of pallial neurons in corvids was much higher than in chicken and pigeons and comparable to those of ostriches. However, neuron numbers in the associative mesopallium and nidopallium were twice as high in corvids and, in correlation with these associative areas, the corvid subpallium also contained high neuron numbers. These findings support our hypothesis that large absolute numbers of associative pallial neurons contribute to cognitive flexibility and complexity and are key to explain why crows are smart. Since meso‐/nidopallial and subpallial areas scale jointly, it is conceivable that associative pallio‐striatal loops play a similar role in executive decision making as described in primates. Abstract : Corvids possess cognitive skills, matching those of nonhuman primates. Here we investigated the number of neurons and their distribution over six telencephalic areas in three corvid and three non‐corvid species to check, if higher amounts of neurons in associative areas could drive cognitive performance in corvids. Indeed, neuron numbers in the associative mesopallium and nidopallium were twice as high in corvids in comparison to non‐corvids possibly contributing to cognitive flexibility and complexity in these species.